A centre of wonders : the body in early America - Lindman, Janet Moore; Tarter, Michele Lise, 1960- (Cornell University Press, 2001)
Images of bodies and bodily practices abound in early America: from spirit possession, Fasting Days, and infanticide to running the gauntlet, going "naked as a sign," flogging, bundling, and scalping. All have implications for the study of gender, sexuality, masculinity, illness, the "body politic," spirituality, race, and slavery. The first book devoted solely to the history and theory of the body in early American cultural studies brings together authors representing diverse academic disciplines. Drawing on a wide range of archival sources-including itinerant ministers' journals, Revolutionary tracts and broadsides, advice manuals, and household inventories-they approach the theoretical analysis of the body in exciting new ways. A Centre of Wonders covers such varied topics as dance and movement among Native Americans; invading witch bodies in architecture and household spaces; rituals of baptism, conversion, and church discipline; eighteenth-century women's journaling; and the body as a rhetorical device in the language of diplomacy